TEKNOLOGI PEMISAHAN SENYAWA AROMA KERAS MENYENGAT PADA ASAP CAIR TEMPURUNG KELAPA DENGAN METODE REDISTILASI DAN ADSORP - , SYAHRAENI KADIR; , Prof. Dr. Ir. Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The role of liquid smoke as aroma maker in foods has some advantages : (1) relatively safely for health, (2) controllable concentration of liquid smoke used and more similar product quality, (3) environmentally friendly, (4) low cost vaporing, (5) easy to use and (6) broad range usage. As a aroma maker, dilution methode of the crude is usually do, but it has disadvantages in low rate of aroma contributor compounds. However, its contribution to compose element vapor aroma is great and so compound of polycyclic aromatic hydrocarbons. Based on the description, the separation of sharp aroma compounds was conducted in liquid smoke of hybrid coconut shell based on boiling point, polarity and hydrophobicity with redistillation and adsorption method. In general, this research aims to separate sharp aroma compounds in liquid smoke of hybrid coconut shell with redistillation and adsorption method to produce soft aroma of liquid smoke. In particular, this research aimed to : (1) separating phenolic compound of low and high boiling point as contributor to sharp aroma of liquid smoke of hybrid coconut shell with redistillation method in medium temperature of 90-130 o C, (2) evaluating physicochemical property and sensory capacity of liquid smoke of coconut shell resulted from the redistillation in medium temperature, (3) separating acid compound as contributor to sharp aroma in liquid smoke of coconut shell with adsorption in zeolite, and (4) evaluating physicochemical property and sensory capacity of liquid smoke of hybrid coconut shell resulted from adsorption in zeolite. This research consist of five steps, namely : (1) preparation of raw liquid smoke used in redistillation and adsorption process, (2) redistillation of liquid smoke in medium temperature (90-130 o C) and 10 minutes interval from early condensation until no drop condensate using a coolant temperatures above 10 o C, (3) liquid smoke redistillation in medium temperature (90-130 o C) and 10 minutes interval using a coolant temperatures below 10 o C system, (4) equilibrium of liquid smoke adsorption in active carbon, (5) liquid smoke adsorption in active carbon and zeolite with pH 2-6. All experiments were done in three replications, except in sensory test. Parameters of liquid smoke resulted from redistillation and adsorption include physicochemical properties of liquid smoke (pH, color spectrum, phenolic compound, carbonyl, titrable acid, profile of compound composing the liquid smoke with GC MS, and benzo[a]pyrene analysis), sensory evaluation for liquid smoke aroma intensity, color and panelists acceptance level. Data obtained was analyzed by using SPSS 16 and advance test with 1% DMRT. The separation of sharp aroma in liquid smoke of hybrid coconut shell with adsorption method in zeolite in pH 2 fraction III and pH 3 in fraction IV and V can separated carbamate acid, propionate, p-cresol, hydroquinone, pyrocatechol and pmethylguaiacol. Characteristic of these fraction have phenolic, carbonyl and acid level of 0,16-0,42%